Spectrophotometric Study of U(VI) with 2-Hydroxy-4-Chloro-5-Methylpropiophenone Oxime - S. Bharadwaj, Punita; Naik, H.B. (Asian Journal of Chemistry, 2010)
In view of the growing importance of o-hydroxy ketoxime as analytical reagent, we have applied 2-hydroxy-4-chloro-5-methylpropiophenone oxime (HCMPOX) for determination of U(VI) spectrophotometrically. Stiochiometry of the complex was studied by continuous variation, the mole ratio and the slope ratio methods which comes out to be 1 : 2 (metal : ligand). Absence isobestic point shows that single complex species exists. The stability constant of the complex is found to be 1.64 x 106. The structure of the complex was also studied by infrared spectra and magnetic susceptible data.